2012
DOI: 10.1111/j.1365-2621.2012.03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and polyphenol contents in Brazilian green propolis extracts prepared with the use of ethanol and water as solvents in different pH values

Abstract: Propolis is a natural product with a variable and complex chemical composition associated with its high concentration on polyphenolic compounds. The effect of pH variation (2.0, 3.0, 4.3, 6.0 and 8.0) during aqueous and ethanolic propolis extraction was studied for up to 10 days. Total phenols and flavonoids contents were measured for the extracts by spectrophotometric assays. Antioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) and ferric thiocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 41 publications
11
39
0
6
Order By: Relevance
“…The ethanol extract of propolis showed a phenolic compound concentration of 55.5 ± 1.6 mg gallic acid per gram of extract. The concentration of these compounds can vary with different types of propolis, the region, and the environmental conditions in which the resin is collected, as well as the parameters of solvent used for the extraction . Ahn et al observed values between 42.9 and 302.0 mg gallic acid per gram of extract for propolis from different regions of China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethanol extract of propolis showed a phenolic compound concentration of 55.5 ± 1.6 mg gallic acid per gram of extract. The concentration of these compounds can vary with different types of propolis, the region, and the environmental conditions in which the resin is collected, as well as the parameters of solvent used for the extraction . Ahn et al observed values between 42.9 and 302.0 mg gallic acid per gram of extract for propolis from different regions of China.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of these compounds can vary with different types of propolis, the region, and the environmental conditions in which the resin is collected, 44 as well as the parameters of solvent used for the extraction. 45 Ahn et al 46 observed values between 42.9 and 302.0 mg gallic acid per gram of extract for propolis from different regions of China. Potkonjak et al 47 observed values similar to those obtained in this study for an extract of propolis produced in Serbia.…”
Section: Characterization Of the Ethanol Extract Of Propolismentioning
confidence: 99%
“…It is collected by bees from flowers, buds, and exudates of plants and is known to have a broad spectrum of biological properties (Mello and Hubinger, 2012;Toreti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The quality and amount of propolis produced are linked to seasonal variations, methods of collection (Inoue et al, 2007;Toreti et al, 2013), geographical diversity, plant sources, and bee species (Mello and Hubinger, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flavonoids and phenolic acids in green propolis have antifungal activities for typical agricultural, food, medical and odontological fungi (Ngatu et al, 2011;Freires et al, 2016;Martini et al, 2017). However, propolis is a tough resin that cannot be consumed in its natural form; thus, resin is typically transformed into a powder and extracted in an alcoholic or aqueous medium (Mello and Hubinger, 2012). Process conditions are important to allow extraction of most bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%